Urine glyphosate exposure and serum sex hormone disruption within the 2013–2014 National Health and Nutrition Examination survey (NHANES). (March 2023) - Geier, David A.; Geier, Mark R.
Abstract: Glyphosate-based herbicides (GBHs) are one of the most commonly used herbicides worldwide. Numerous in vitro and in vivo model system studies have demonstrated endocrine-disrupting chemical (EDC) properties associated with glyphosate/GBH exposure. The present hypothesis-testing study evaluated the potential inverse dose-dependent relationship between increasing urinary glyphosate and decreasing concentrations of blood sex hormones. Demographic and newly available lab test data from the 2013–2014 National Health and Nutrition Examination Survey (NHANES) were analyzed with survey regression modeling (adjusted for age, gender, race, and country of birth) in Statistical Analysis System (SAS) software. A total of 225, 615, 858 weighted-persons (sample n = 2130 persons) were examined for concentrations of urinary glyphosate and serum sex hormones (including: total testosterone, total estradiol, and sex hormone binding globulin (SHBG)) among males and females, 6 years-old or older. This study revealed about 82% of the population of the United States examined had detectable urinary concentrations of glyphosate. A significant inverse correlation between concentrations of glyphosate and total estradiol and a trend towards an inverse correlation between concentrations of glyphosate and total testosterone were observed. Concentrations of SHBG and glyphosate did not correlate. Ratios of total testosterone:SHBG and total estradiol:SHBG (estimating the fraction of active sex hormones in the blood) were significantly inversely correlated with urinary concentrations of glyphosate. This epidemiological study associates widespread and ongoing glyphosate/GBH exposures with human endocrine-disruptions. Future studies should examine these phenomena in other databases and other endocrine-related disorders. Graphical abstract: Image 1 Highlights: Glyphosate-based herbicides are among the most commonly used herbicides. Glyphosate is widely present in the environment. Glyphosate exposure was linked to endocrine-disruption. Urinary glyphosate is detectable in ∼82% of the US population. Urinary glyphosate is inversely related to blood sex hormones amounts.